Analisis Pelaksanaan Universal Precaution pada Pelayanan Kesehatan Gigi - Oktarina Dwi Ratna Soeryandari (Berita Kedokteran Masyarakat (BKM), 2008)
Background: At Health Centers diseases could be directly or indirectly transmitted because the clinical procedures are not followed or carelessness of health workers. The universal precautions are done to protect patients and health workers from communicable diseases in health facilities, including dental services.Method:  This was an observational study with explanatory methods. Data were collected by interview, questionnaires, observation, focus group discussion, and data secondary. The study was conducted in 30 Health Centers in Surabaya City. Subjects were 30 dentists from 30 health centers. The dental services with the universal precaution procedures given by the dentists were observed. Data were analyzed descriptively.Result: Results of the study showed the knowledge of 50% respondents was not good and 80% of the dentists skillfully conducted the universal precaution indicators. Based on organization factors, the majority of the respondents had received training on the universal precaution but supervision had not been done routinely. Eighty three point three percents (83.3%) dentists used gloves every time give service, 80% of the instruments were in sterilized condition, 30% of the centers had medical waste baskets or for needles. Based on work load, it was increasing if the patients increased because of the  limited instruments, especially sterilization instruments had not provided in all health centers. The Standard Operational Procedures were hanged just in some Health Centers.Conclusion: The universal precaution in the dental clinics had not been 100% conducted in the Health Centers because of the lack of knowledge and training or continued education and also supervision and evaluation by the District Health Office. Besides there were a higher work load of the dentists in conducting their works and lack of dental instruments so that these risk of infections in the Health Centers and their environments.Keywords: universal precaution, dental personnel